How reliably do rheumatologists measure shoulder movement?. Issue 7 (1st July 2002) - Hoving, J L; Buchbinder, R; Green, S; Forbes, A; Bellamy, N; Brand, C; Buchanan, R; Hall, S; Patrick, M; Ryan, P; Stockman, A
Abstract : Objective: To assess the intrarater and interrater reliability among rheumatologists of a standardised protocol for measurement of shoulder movements using a gravity inclinometer. Methods: After instruction, six rheumatologists independently assessed eight movements of the shoulder, including total and glenohumeral flexion, total and glenohumeral abduction, external rotation in neutral and in abduction, internal rotation in abduction and hand behind back, in random order in six patients with shoulder pain and stiffness according to a 6×6 Latin square design using a standardised protocol. These assessments were then repeated. Analysis of variance was used to partition total variability into components of variance in order to calculate intraclass correlation coefficients (ICCs). Results: The intrarater and interrater reliability of different shoulder movements varied widely. The movement of hand behind back and total shoulder flexion yielded the highest ICC scores for both intrarater reliability (0.91 and 0.83, respectively) and interrater reliability (0.80 and 0.72, respectively). Low ICC scores were found for the movements of glenohumeral abduction, external rotation in abduction, and internal rotation in abduction (intrarater ICCs 0.35, 0.43, and 0.32, respectively), and external rotation in neutral, external rotation in abduction, and internal rotation in abduction (interrater ICCs 0.29, 0.11, and 0.06, respectively). Conclusions: The measurement of shoulder movements using a standardised protocol by rheumatologists produced variable intrarater and interrater reliability. Reasonable reliability was obtained only for the movement of hand behind back and total shoulder flexion.